1986
DOI: 10.1007/bf00237749
|View full text |Cite
|
Sign up to set email alerts
|

M.I.T./Canadian vestibular experiments on the Spacelab-1 mission: 4. Space motion sickness: symptoms, stimuli, and predictability

Abstract: Space sickness symptoms were observed by 4 specially trained observers on Spacelab-1. Three reported persistent symptoms, and vomited repeatedly during the first and/or second day of flight. Head movements on all axes were provocative, particularly in pitch and roll. Head acceleration data recorded from 2 symptomatic crewmen showed that after several hours of physical activity in orbit, symptoms appeared, and thereafter both crewmen were compelled to limit head movements. Firm body contact with motionless surf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
0

Year Published

1991
1991
2017
2017

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(51 citation statements)
references
References 16 publications
1
50
0
Order By: Relevance
“…This may indicate that the lack of con®rming otolith cues during head pitch is particularly provocative (Oman et al 1986). The rationale behind CVT is that tolerance to the con¯ict between the semicircular canals and nonconforming otolith cues generated by Coriolis and cross-coupled angular accelerations on Earth would transfer to weightlessness conditions (Popov et al 1970).…”
Section: Introductionmentioning
confidence: 97%
“…This may indicate that the lack of con®rming otolith cues during head pitch is particularly provocative (Oman et al 1986). The rationale behind CVT is that tolerance to the con¯ict between the semicircular canals and nonconforming otolith cues generated by Coriolis and cross-coupled angular accelerations on Earth would transfer to weightlessness conditions (Popov et al 1970).…”
Section: Introductionmentioning
confidence: 97%
“…Because gravity is such an important factor in determining the orientational structure of the environment, in a weightless environment where there is no perceived gravitational vertical, the astronauts' reference frames seems to be based predominantly on features of the visual environment that normally align with gravity, such as spacecraft interiors, images of trees, and other crewmembers [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…Although metoclopramide is an effective antiemetic agent that enhances gastric emptying and prevents cancer chemotherapy-induced emesis, some studies [92,93] have been unable to demonstrate any significant effects of this drug in the case of motion sickness. Only Rubio et al [94] found metoclopramide to be more effective than diphenhydramine and placebo in the treatment of motion sickness.…”
Section: Prevention and Treatment Of Motion Sicknessmentioning
confidence: 99%